Comparative chloroplast genomes: insights into the identification and phylogeny of rapid radiation genus Rhodiola - Liu, Jinxin; Zang, Erhuan; Tian, Yu; Zhang, Liqiu; Li, Yimin; Shi, Linchun; Xu, Lijia; Xiao, Peigen (Frontiers in Plant Science, 2024)
Rhodiola L. is a genus exhibiting rapid radiation and represents a typical case for studying plastid gene adaptation in species that spread from high altitudes to low altitudes. In this study, 23 samples of 18 Rhodiola species were collected from the Qinghai-Tibetan Plateau and five scattered alpine areas, and the plastid genomes (plastomes) of these species were sequenced, annotated, and compared between high-altitude and widely distributed groups. The plastomes of Rhodiola were found to be highly conserved in terms of gene size, content, and order but highly variable in several lineage-specific features, such as codon usage bias, IR boundary shifting, and distinct repeat sequence structures binding to SSRs. Codon usage in the genes of photosystem II exhibited an obvious preference, reflecting significant environmental adaptation pressures. In this study, three repeat regions compounded with trinucleotide and mononucleotide repeats were found for the first time in R. forrestii, R. himalensis, and R. yunnanensis. High-variability regions such as ndhF, ycf1, trnH-psbA, and rpoC1-rpoB were screened, laying the foundation for the precise identification of these species. The phylogenetic analysis revealed the occurrence of cyto-nuclear discordance, likely originating from the frequent interspecific hybridization events observed within Rhodiola species during rapid radiation. Dioecious and hermaphrodite species can be broadly categorized into two subclades, probably they have different environmental adaptation strategies in response to climate change. In addition, the phylogenetic tree supported the monophyly of R. forrestii and R. yunnanensis, which compose R. Sect. Pseudorhodiola. In conclusion, plastome data enrich the genetic information available for the Rhodiola genus and may provide insight into species migration events during climate change.